An assessment of wealth taxes in a joint income-wealth perspective - Sarah Kuypers; Francesco Figari; Gerlinde Verbist (University of Essex, Institute for Social and Economic Research (ISER), 2020)
Many researchers and policymakers have made strong arguments for broadening the taxes on wealth and its returns. Although the theoretical literature on (optimal) wealth taxation is growing, there exists a large void in empirical research. This paper addresses this void by analysing the redistributive and budgetary impact of wealth taxes in six European countries using the perspective of the joint distribution of income and wealth. We use data from the Eurosystem Household Finance and Consumption Survey (HFCS) and EUROMOD. We show that existing wealth taxes do not achieve any significant redistribution. Although they are in most cases strongly progressive, the low redistributive effect is mainly due to their small size. Moreover, there is a lack of neutrality in the tax system with regard to the source from which households draw their financial living standard: income or wealth. Hence, existing wealth taxes score badly on both vertical and horizontal equity grounds
Keywords: C15; D31; H23; H24; 330; redistribution; income tax; wealth tax; microsimulation